Time Loop Plot Structure Pattern in the Films Edge of Tomorrow (2014), Happy Death Day (2017) and Palm Springs (2020) - Nugroho, Agustinus Dwi; Ridwan, M. Alif Wijaya (Capture : Jurnal Seni Media Rekam, 2024)
Exploration of plot development patterns in narrative structure can be seen from the Time Loop Plot which is used in several films in a very unique way. This plot pattern emphasizes a character trapped in space and time that repeats itself continuously. This qualitative research uses an observational approach that focuses on observing Time Loop Plot patterns and connecting them with three different genre variants, namely Edge of Tomorrow (action-science fiction), Happy Death Day (thriller-horror), and Palm Spring (roman-comedy). This research aims to obtain an overview of the narrative structure pattern "Time Loop Plot" which can be applied in various genres through a visual element approach, as well as looking for a storytelling motif in the application of this plot development pattern in each different genre, using the approach of narrative theory and aesthetics. The results of this research reveal a pattern which shows that the time loop plot pattern is character-driven by the main character. The relationship with genre shows a pattern that differences in genre in the application of time loop plots will result in differences in the development of tone and mood in the film. ​Keywords: narrative, plot, time loop, genre